Haunted :|tracing the figure of the ghost in drama - Kılınç, Burcu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
In the long interval between the beginnings of the drama and the contemporary stage, the ghost, with its fundamental liminality, remains one of the most ubiquitous and relevant supernatural figures that appear on theatrical space. As a quintessential figure of ‘return’, the ghost, within the plays it appears in, acts as a valid instrument to bring back to surface the unresolved tensions resulting from major social shifts or national cataclysms in order to acknowledge the existence of these tensions and perhaps, even resolve them. The present study explores the manifestations of the ghost on the theatrical stage of three distinct periods, Ancient Greek, Elizabethan/Jacobean England, and Contemporary (post-1960s) American. In the analysis of the selected plays, the figure of the ghost and its function is examined in relation to notions of justice, memory, legacy and identity. The aim of this comparative study is to trace the continuations and the alterations with respect to the conception and the function of the ghost through this historical trajectory, as the figure continues to probe and bring to surface unresolved tensions.
Keywords: Theater.